EXPERIMENTAL SUBSTANTIATION FOR XENOTRANSPLANTA-TION EFFICIENCY OF CRYOPRESERVED CULTURES OF THE PANCREAS ISLET TISSUE MICROFRAGMENTS AT DIABETES MELLITUS - Pobelensky, O.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Experimental investigations of transplantation effect under the capsule of kidney of the newborn piglet’s pancreas cryopreserved microfragments on glycemia level and the indices of lipid peroxidation in rats with alloxan diabetes were carried-out in the work.